2012
DOI: 10.2174/092986712800269362
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in Gynecological Pathology

Abstract: microRNAs (miRNAs) are 21-22 nucleotide non-coding RNAs that regulate gene expression and play fundamental roles in biological processes. These small molecules bind to target mRNAs, leading to translational repression and/or mRNA degradation. Aberrant miRNA expression is associated with several human diseases such as cancer, cardiovascular disorders, inflammatory diseases and gynecological pathology. The present article reviews the role of miRNAs in four gynecological disorders that affect the ovary or the ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 1 publication
1
62
0
4
Order By: Relevance
“…Corresponding with these findings Torres et al reported a significant up-regulation of all miR-200 family members, mostly pronounced in the early phase of EEC [21]. Additionally, an over expression was found to encounter miR-205 and miR-210, suggesting them to be selected as biomarkers for the early diagnosis and prognosis of EC [22]. Xiong and colleges studied miRNAs in relation to early stage (stage I) EEC, and identified a deregulation of hsa-miR-196a-5p, hsa-miR-328-3p, hsa-miR-337-3p, and hsa-miR-181c-3p indicating their clinical value as potential diagnostic markers [18].…”
Section: Micrornasmentioning
confidence: 63%
See 4 more Smart Citations
“…Corresponding with these findings Torres et al reported a significant up-regulation of all miR-200 family members, mostly pronounced in the early phase of EEC [21]. Additionally, an over expression was found to encounter miR-205 and miR-210, suggesting them to be selected as biomarkers for the early diagnosis and prognosis of EC [22]. Xiong and colleges studied miRNAs in relation to early stage (stage I) EEC, and identified a deregulation of hsa-miR-196a-5p, hsa-miR-328-3p, hsa-miR-337-3p, and hsa-miR-181c-3p indicating their clinical value as potential diagnostic markers [18].…”
Section: Micrornasmentioning
confidence: 63%
“…Several authors have implied that an up-regulation of AEG-1 enhances characteristics of malignant aggressiveness making it an independent prognostic factor for unfavourable clinical outcome. This suggests that AEG-1 is valuable as a prognostic biomarker of disease progression and survival in patients with EC [16][17][18].…”
Section: Biomarkers With Diagnostic Prognostic and Therapeutic Valuementioning
confidence: 96%
See 3 more Smart Citations